Digitalizing Sharia Fintech: Adapting Islamic Economic Principles for Millennials - Yeny Fitriyani (Journal of Halal Review, 2025)
Objective: This study aims to explore the adaptation of economic principles from Prophet Muhammad within Islamic fintech, examining its relevance to Indonesia’s millennial generation and how these platforms can support MSME growth, enhance financial inclusion, and adhere to sharia principles in the digital era. Research Design & Methods: This research uses a qualitative method with a literature study approach to analyze narrative data from various sources, thus enabling a comprehensive understanding of the phenomenon by integrating theoretical and practical perspectives. Findings: The study results show that Islamic fintech platforms, which adhere to Sharia principles such as the prohibition of usury and ethical transactions, offer a suitable alternative to conventional finance for Indonesia’s millennial generation, with its digital fluency and openness to innovation, is ready to adopt Islamic fintech such as peer-to-peer lending and crowdfunding to improve financial inclusion, MSME accessibility, and sharia-based economic growth. Implications & Recommendations: This study recommends that Islamic financial institutions invest in user-friendly, transparent fintech platforms, while policymakers should create regulations that support Islamic fintech development and financial inclusion for MSMEs. Additionally, Islamic fintech platforms should integrate educational features on Sharia principles to promote ethical financial behavior among millennials. Contribution & Value Added: This study contributes to the Islamic fintech literature by bridging traditional Islamic economic principles with modern fintech practices. It offers a model for Muslim-majority countries to modernize financial systems focused on financial inclusion, MSME development, sustainable innovation, and social welfare.